THE POP VOCAL DUET IN THE REPUBLIC OF MOLDOVA - MUNTEANU, ANGELICA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2021)
Th is article presents a brief overview of the pop vocal duets in the Republic of Moldova, which experienced two stages of development (the 1960s-1990s and the 2000s) being marked by the emergence of new artistic tandems and works created for them. Two main types of vocal duets appeared and affi rmed themselves in Moldovan vocal light music during each of the mentioned periods: permanent duets (which were formed and existed for a certain period of time with a duet status) and the temporary ones (that were created on the occasion of some events or for the performance of a specifi c piece).